AN ANALYSIS OF GRAMMATICAL COHESION OF DESCRIPTIVETEXT FOR THE SEVENTH YEAR STUDENTS OF JUNIOR HIGH SCHOOL - Miranda Putri; Syofia Delfi; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to find out the grammatical cohesion of descriptive texts of students’ textbook “When English Rings A Bell” for the Seventh Year Students of Junior High School published by Pusat Kurikulum and Perbukuan Kemendikbud. This research uses a descriptive qualitative research. This method was pointed out to obtain clear description of the object base on the actual fact and valid data. The technique of analysis involved agglomerating, identifying, counting and making interpretation. The writer uses M.A.K Halliday and Hasan’s theory to analyze the types of grammatical cohesion. Based on the result of investigation that the writer has done, the grammatical cohesion of descriptive texts of English textbook "When English Rings a Bell" is cohesive text in “poor” categorize, since the rate of the percentage is 22.1%. It can be concluded that “When English Rings a Bell” textbook is less of cohesive device. It is suggested that grammatical cohesion in a text has important role as stated by Hasan (1968) cohesion occurs in a text if it has texture. In other words, a text is cohesive when the stretches of language are hung together with ties and give it meaning.Key Words: Analysis, Grammatical Cohesion, Descriptive Text